Implantação do indicador de taxa de utilização de mão de obra em uma empresa prestadora de serviços offshore - Bellódi, Rômulo Donizetti (2024)
The offshore industry faces significant challenges in workforce management due to the complexity of different types of employment contracts. Implementing a labor utilization rate indicator is crucial for assessing efficiency and productivity, but it encounters barriers due to the particularities of Onshore and Offshore regimes. The DMAIC methodology (Define, Measure, Analyze, Improve, Control) was chosen as the most effective solution because it provides a structured and results-oriented approach. It is expected that applying this methodology will find an appropriate method for measuring human resource utilization and provide valuable information for decision-making within the company. Preliminary analysis showed a trend of the indicator within the limits established as healthy for the organization and professionals, but it also highlighted the need for improvements in resource management.